THE EFFECT OF EMPLOYEE ENGAGEMENT, WORK ENVIRONMENT AND ORGANIZATIONAL LEARNING ON ORGANIZATIONAL COMMITMENT IN MEDIKA LESTARI HOSPITAL CILEDUG - Jesika; Sandra Dew; Intan Silvy (CV. Bunda Ratu, 2024)
Health care delivery systems face ongoing challenges caused by a number of factors. These include ongoing technological changes, clinical advances, and increasing public expectations of healthcare services. Health facility managers and leaders are faced with an organizational model that, in addition to the usual values of effectiveness and efficiency, must meet excellent standards of clinical care. This research aims to determine the influence of employee engagement, work environment and organizational learning on organizational commitment at Medika Lestari Ciledug Hospital. This research is a descriptive analytical study with a cross sectional study design with 92 respondents who are employees at Medika Lestari Ciledug Hospital. This research draws samples using the Slovin formula. The independent variables in this research are employee engagement, work environment and organizational learning. Organizational commitment as the dependent variable. The tool used to collect data in this research is a questionnaire. Data were analyzed using the causality method. The research results show that employee engagement has a significant positive effect on organizational commitment. It was also found that the Work Environment has a significant positive impact on organizational commitment. Finally, the results of this research confirm that Organizational learnings have a significant positive effect on organizational commitment. These findings provide useful insights and suggestions for management in Hospitals to learn to develop organizational Commitment among their employees by adopting effective human resource practices which can ultimately lead to organizational competitiveness and improved performance